2010
DOI: 10.1007/s10856-010-4133-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of silver nanoparticles with antimicrobial activities and the researches of their biocompatibilities

Abstract: Silver nanoparticles were prepared by chemical reduction method using chitosan as stabilizer and ascorbic acid as reducing agent in this work. The silver/chitosan nanocomposites were characterized in terms of their particle sizes and morphology by using UV spectrophotometer, nano-grainsize analyzer, and transmission electron microscopy. Antibacterial activities of these nanocomposites were carried out for Staphylococcus aureus and Escherichia coli. The silver nanoparticles exhibited significantly inhibition ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 30 publications
3
94
1
1
Order By: Relevance
“…The authors suggested that the difference in MIC values could be related to the variation in nanoparticle size and shape. Silver/chitosan nanocomposites were characterized by Cao et al [122] in terms of their particle sizes and morphology. The antibacterial activities of these nanocomposites against S. aureus and E. coli were investigated.…”
Section: Influence Of the Preparation Techniques Of Chitin/chitosan-bmentioning
confidence: 99%
“…The authors suggested that the difference in MIC values could be related to the variation in nanoparticle size and shape. Silver/chitosan nanocomposites were characterized by Cao et al [122] in terms of their particle sizes and morphology. The antibacterial activities of these nanocomposites against S. aureus and E. coli were investigated.…”
Section: Influence Of the Preparation Techniques Of Chitin/chitosan-bmentioning
confidence: 99%
“…15,22 These studies showed potential antibacterial activity against both Gram-negative and Gram-positive bacteria. 14,19,[23][24][25] Any metal nanoparticle could be evaluated for antiviral activity; however, little effort has already been devoted to the determination of nanoparticle's antiviral activity and their interactions with viruses.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Ag-NPs have been widely used in various applications because of their well-known effectiveness in biomedical (Cao et al, 2010), electronic, catalysis and optical applications (Hayward et al, 2000). In particular, the outstanding antimicrobial properties of AgNPs have led to the development of variety of silver nanoparticle products including nanosilver-coated bandages, surgical instruments, contraceptive devices and dental implants (Lohse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%